Penetapan Harga Pokok Penjualan (HPP) Perbankan Syariah Menurut Perspektif Etika Bisnis Islam - Lely Suryani; Sasmita Sari Ardaninggar (ITB AAS INDONESIA Surakarta, 2022)
Economic progress today cannot be separated from the banking world. The role of banks as financial intermediaries keeps the wheels of a country's economy running by bringing together those who need funds with those who have funds. In Indonesia, the prospect of Islamic banking is getting brighter and more promising. It is believed that Islamic banks in this country will continue to grow and develop in the future. There are several sharia banking products, namely in the form of partnerships (musyarakah and mudharabah), sellers-buyers (murabahah, greetings and istishna), leases (ijarah), debtors - creditors; in terms of equity holder (qard). Price is a component that directly affects the company's profit. Because pricing affects total revenue and costs, pricing decisions and strategies play an essential role in every company. The calculation results of the profit of several Islamic banks showed a profit of more than 100%, where PT Muamalat Indonesia obtained the minor profit in 2020 at 184%, and PT Bank Syariah Bukopin acquired the most significant profit in 2020 at 381%. In Islam, it is recommended that traders not take profits excessively. This means that when you make a profit that is too large, it has fallen into taking other people's property by vanity, not an exchange category. on the other hand, Islam does not provide certain limits in taking profit as long as it follows sharia principles. Islam only provides business ethics for business actors and consumers.